2014
DOI: 10.1088/0964-1726/23/6/065007
|View full text |Cite
|
Sign up to set email alerts
|

Towards the development of active compression bandages using dielectric elastomer actuators

Abstract: Disorders associated with the lower extremity venous system are common and significantly affect the quality of life of a large number of individuals. These disorders include orthostatic hypotension, oedema, deep vein thrombosis and a number of other conditions related to insufficient venous blood return. The common recommended treatment for these disorders is the use of hosiery compression stockings. In this research, an active compression bandage (ACB) based on the technology of dielectric elastomeric actuato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 30 publications
0
62
1
Order By: Relevance
“…The second evidence is that by adopting the multilayer design reported above and different constitutive materials, it was possible to achieve a higher contact pressure drop as compared to previous studies. Indeed, the best performing active bandage prototype reported in [10] allowed for achieving an initial contact pressure of 2.87 kPa and a drop to 2.73 kPa, corresponding to a 5.2% decrease, for a voltage of 11.3 kV; in comparison, the active bandage prototypes presented here allowed for contact pressures ranging from 6.57 kPa to 6.78 kPa and, respectively, pressure drops from 8.2% to 10.2%, for a voltage of 8.5 kV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second evidence is that by adopting the multilayer design reported above and different constitutive materials, it was possible to achieve a higher contact pressure drop as compared to previous studies. Indeed, the best performing active bandage prototype reported in [10] allowed for achieving an initial contact pressure of 2.87 kPa and a drop to 2.73 kPa, corresponding to a 5.2% decrease, for a voltage of 11.3 kV; in comparison, the active bandage prototypes presented here allowed for contact pressures ranging from 6.57 kPa to 6.78 kPa and, respectively, pressure drops from 8.2% to 10.2%, for a voltage of 8.5 kV.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, prior to this work other investigators have reported on the use of DE actuators to develop active bandages [10], [11]. The peculiarities of the approach described here are: 1) two active layers were stacked together to increase the strength of the system; 2) the active layers were made of an acrylic elastomer film showing one of the highest electromechanical transduction performance, in terms of maximum achievable strains and stresses; 3) stiffening sticks were used to maximise actuation along the radial direction; 4) two thick and soft passive layers were used as interfaces with suitable properties in terms of mechanical compliance and electrical safety.…”
Section: Active Bandage Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the wearable interface should not interfere with the wearer's movement, while maintaining comfort. Thus, there are many advantages for using DEAs for wearable interfaces, such as their small size, flexibility, softness, and customizability [119][120][121][122][123][124][125][126][127][128][129][130][131].…”
Section: Wearable User Interfacementioning
confidence: 99%
“…An active compression bandage using DEAs was suggested. It can be taken on and off easily, fits different calf sizes, and is provided in small size modules [128]. Also, the compression magnitude of the bandage can be modulated by changing the initial pre-stretch ratio or working voltage.…”
Section: Wearable User Interfacementioning
confidence: 99%